Perinatal factors associated with subsequent diabetes mellitus in the child: record linkage study. - Ievins, R; Roberts, SE; Goldacre, M (2007)
AIMS: To report on associations between perinatal factors and the subsequent development of diabetes mellitus under the age of 30 years in the offspring. METHODS: Analysis of linked hospital statistical records, comparing perinatal factors relating to the birth of 518 people admitted to hospital for diabetes with the same factors in 292 845 others, in a defined population in southern England from 1963 to 1999. RESULTS: Diabetes mellitus was much more common in children of mothers with diabetes than in others (odds ratio 6.42; 95% confidence interval 4.18-9.86). There was no significant association with birthweight or gestational age separately. Diabetes was more common in those in the highest quintile of 'birthweight for gestational age' compared with the lowest four quintiles combined (odds ratio 1.33; 95% confidence interval 1.08-1.64), but there was no consistent gradient of increasing frequency of diabetes across the lowest four quintiles. There were no significant associations between diabetes and mothers' age, parity, social class, or smoking during pregnancy, or between babies' mode of delivery or any other perinatal factors investigated. All results were similar when the analysis was confined to diabetes in people aged < 15 years. CONCLUSIONS: We found a strong association between diabetes in the child-mainly, if not entirely Type 1 diabetes-and maternal diabetes. Diabetes was slightly more common in the heaviest quintile of birthweight for gestational age than in other quintiles. There were no significant associations between diabetes and the other perinatal factors studied.